Sandal Mop - Rosman, Nurul Najwa; Mohd Faizal, Damia Adha; Mohd Sabri, Nur Afrina; Ja'afar, Izzaty Natasha; Mohd Amin, Zharif Hilman; Huazaimie, Nurqistina; Ramly, Fariha Aiza (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
The Sandal Mop is an innovative cleaning equipment that revolutionises conventional footwear by turning it into a versatile cleaning tool. The product ingeniously combines the convenience of wearing sandals with cutting-edge cleaning technology, transforming walking and engaging in activities into an efficient cleaning method. The Sandal Mop provides a cost-effective, versatile, and environmentally friendly option for maintaining cleanliness in homes and businesses by combining advanced cleaning technologies with everyday sandals. The revolutionary design of this product harnesses the inherent movement of walking to efficiently clean a wide range of surfaces, such as sealed wood, vinyl, tiles, marbles, and glass. The removable microfiber mop guarantees compatibility with sensitive skin, making it appropriate for persons with allergies or dermatitis. The Sandal Mop promotes a global adoption of healthier, cleaner, and more environmentally friendly lifestyles by emphasising simplicity, efficacy, and eco-friendliness. Cleaning has never been more convenient or entertaining, and its inspiring people all around the globe to live greener, healthier lives.